Gestão integrada de resíduos sólidos urbanos : análise de viabilidade econômica de cenários para um município de médio porte - Berticelli, Ritielli (2016)
The integrated and sustainable management of municipal solid waste (MSW) is justified because of the situation of depletion and impairment of natural resources, social, environmental and economic problems of disposal. Noting the environmental impacts that the MSW can cause and the precariousness of the current situation in their management process occurred in the city of Passo Fundo/RS, alternatives are needed in order to improve their management, increase efficiency and reduce costs by collaborating with the preservation of the environment. Efficient systems of selective collection, environmental awareness and adoption of treatment and final disposal alternatives can significantly reduce the management costs of MSW and its negative impacts. The aim of this study is to evaluate the economic feasibility of targeted scenarios for the management of municipal solid waste in the city of Passo Fundo/RS, checking the possibility of reducing costs by establishing a new dynamic to the municipal policies to propose the integrated action between the services provided to the population, seeking greater efficiency, effectiveness, social integration and sustainability. The methodology was to draw up scenarios with management alternatives. Three scenarios were created: the inertial scenario, which considers the maintenance of the current conditions of the MSW system of the municipality; the emergency scenario, which proposes some adjustments to the current MSW system; and the normative scenario, which proposes the creation of a new model of management of MSW, according to the Law 12.305/2010 to the city of Passo Fundo/RS. The main technical, economic and operational characteristics of these scenarios have been raised, and held the economic feasibility analysis thereof. The research result shows that the regulatory environment is the one with the best economic viability for the municipality. It follows that it is possible to meet the objectives set by the National Solid Waste Policy and at the same time reducing costs to the management of MSW. The results show a 25% reduction in costs with the implementation of the proposed Regulatory Scenario. Thus, the interest of municipal leaders in waste management issue, with the participation of service users and the proper management of resources, it is possible to establish a new dynamic to the municipal policies to MSW